ANALISIS KINERJA SIMPANG TAK BERSINYAL (STUDI KASUS: SIMPANG EMPAT PADANG TINGGI KOTA PAYAKUMBUH) - Agung, Jumatul; Dewi, Selpa; Endri, Endri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The increasing number of vehicles passing through the intersection allows traffic conflicts to occur which affects the quality of the intersection service. Therefore it is necessary to carry out an analysis related to the performance of the intersection, and look for alternatives related to problems at the intersection if necessary. The research location is at the Padang Tinggi intersection, an unsignalized four-arm intersection located in Padang Tinggi Village, West Payakumbuh District. From the method used, namely MKJI 1997, data from the field is needed, in the form of intersection geometric data, environmental conditions, and traffic conditions. From the results of the research and discussion, it was obtained that the degree of saturation (DS) was 0.77, and the delay (D) was 12,530 sec/smp. Because the DS value exceeds the provisions set by MKJI 1997, namely 0.75, which means it is in an unstable condition, an alternative improvement is made by changing the approach width of each intersection arm and a degree of saturation (DS) value is obtained of 0.74, which is already in a stable condition ( DS<0.75), and the delay does not exceed 15 s/pcu.